PENGENALAN BALANCED SCORECARD SEBAGAI STRATEGI ORGANISASI BISNIS - Dini Vientiany; Wahyuni Pohan, Nona Adelia, Julia Barus (CV. Adiba Aisha Amira, 2024)
The aim of this research is to explore the introduction and implementation of the Balanced Scorecard (BSC) as a management strategy in business organizations, as well as evaluate its impact on organizational performance. The Balanced Scorecard is a strategic management tool that helps organizations align business activities with vision and strategy, improve internal and external communications, and monitor organizational performance against strategic goals. This research uses the library research method or literature study to explore the introduction and implementation of the Balanced Scorecard (BSC) as a business organization strategy. This method involves collecting and analyzing data from various relevant literature sources, including books, journal articles, research reports, and other publications related to the Balanced Scorecard and strategic management. The research results show that the introduction of the BSC provides a structured and comprehensive framework for planning and measuring performance. Companies that implement BSC experience improvements in strategy alignment with daily operations, better communication between departments, and increased transparency and accountability. In addition, the company also recorded an increase in achieving strategic goals and improving financial performance. However, challenges faced in BSC implementation include resistance to change, the need for adequate training, and adaptation of the BSC to the company's specific needs